Creative ways to help children regulate and manage anger ideas and activities for working with anger and emotional regulation - Dr. Zandt, Fiona (Jessica Kingsley Publishers, 2024)
"Support children to better understand and manage their anger with this practical guide of therapeutic activities. From exploring a child's first steps in therapy to helping parents and carers with their responses, this book provides practical advice for working with children aged 4-12 and families navigating issues of anger and emotional regulation. The book includes over fifty playful, practical, and purposeful activities to use in therapy. Grounded in theory and research around anger in children, the activities include clear therapeutic rationales for practitioners, considerations for older and younger children, suggestions for the inclusion of parents and carers, and adaptations for online practice. This is the ultimate tool for therapists looking to develop their clinical practice with creative ways to help children manage their anger."